2000
DOI: 10.1006/viro.1999.0146
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Infection Blocks Events in the G1 Phase of the Cell Cycle

Abstract: Infection of cells in G1 phase with herpes simplex virus (HSV) prevents their progression into S phase (de Bruyn Kops, A., and Knipe, D. M., 1988, Cell 55, 857-868). We have examined G1-phase events in infected cells to determine whether this effect was the result of inhibition of G1 phase progression or of entry into S phase. We observed that HSV infection decreased pRb phosphorylation and induced a new phosphorylated form of pRb. Furthermore, HSV infection prevented the normal G1 increases in cyclin D1 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 43 publications
6
58
0
Order By: Relevance
“…The present study was initiated in order to test the hypotheses that the rates of degradation of cyclins D1 and D3 were affected directly by ICP0, and not indirectly by its role in stimulating viral infection, and that any degradation of cdc34 was concordant with an effect on stability of cyclins D1 and D3. The fact that other laboratories have shown that cyclins D1 and D3 are efficiently degraded during HSV-1 infection, even in the presence of ICP0 (1,13), creating an apparent conflict in the literature, is pertinent.…”
mentioning
confidence: 99%
“…The present study was initiated in order to test the hypotheses that the rates of degradation of cyclins D1 and D3 were affected directly by ICP0, and not indirectly by its role in stimulating viral infection, and that any degradation of cdc34 was concordant with an effect on stability of cyclins D1 and D3. The fact that other laboratories have shown that cyclins D1 and D3 are efficiently degraded during HSV-1 infection, even in the presence of ICP0 (1,13), creating an apparent conflict in the literature, is pertinent.…”
mentioning
confidence: 99%
“…In quiescent cells, HSV-1 infection prevents G1 entry by inhibition of cyclin D/CDK4,6-specific and cyclin E/CDK2-specific phosphorylation of the retinoblastoma protein pRb. On the other hand, HSV-1 induces G1/S arrest in dividing cell cultures by inhibition of preexisting cyclin E/CDK2 and cyclin A/CDK2 activities (Ehmann et al, 2000;Song et al, 2000). The ability of HSV-1 to alter cellular environment in order to enhance viral replication has been related to the expression of immediate-early protein ICP0.…”
Section: Herpesvirus Modulation Of the Cell Cyclementioning
confidence: 99%
“…3). Infection with DNA viruses such as herpes simplex virus (HSV), cytomegalovirus (CMV), Eppstein-Barr virus (EBV) and mouse hepatitis virus (MHV) lead to a block in cellular DNA synthesis by G 1 -arrest, [43][44][45][46] most likely to prevent competition of the viral replication machinery with cellular replication. The HSV-encoded ICP0 protein can induce cell cycle arrest by induction of the tumor suppressor p53 and its downstream targets p21, gadd45 and mdm2.…”
Section: Viral Interference With the Cell Cycle Programmentioning
confidence: 99%
“…47 Furthermore, HSV infection results in inhibition of cyclin D-cdk4/6 and cyclin E-cdk2 kinase activity by inhibiting cyclin D1 and cyclin E expression, and decreased Rb phosphorylation. 43 Human cytomegalovirus stimulates p53 activity, leading to a p21-dependent inhibition of cell cycle progression. 48 The EBVencoded protein ZTA was found to cause a G 1 -arrest by inducing p53 and the cdk inhibitors p21 and p27 as well as accumulation of hypophosphorylated (growth-suppressive) Rb.…”
Section: Viral Interference With the Cell Cycle Programmentioning
confidence: 99%